The Lifeworld of Millennial Stage Actors in Metro Manila: A Schutzian Phenomenological Study - Jalaine Joyce V. Malabanan; Jose Mari A. Carpena; Feorillo Petronilo A. Demeterio III (Wacana Seni Journal of Arts Discourse, 2022)
Using the phenomenological method developed by the Austrian-American philosopher and social theorist Alfred Schutz, this article studied the lifeworld of millennial stage actors in Metro Manila, Philippines. Lifeworld is the meaning-giving sphere of common sense that is shared by individuals from a given social group. Using the data gathered from key informant interviews with 12 professional actors and five consociates from the said locale, we investigated how these millennial actors started their careers in the theatre industry, how they perceived theatre in general and Philippine theatre in particular, how they experienced the challenges and difficulties in their careers, how they were motivated to persevere, and how they envisioned their long-term future in the same industry. This article contributes to the sparse literature on the lives of contemporary professional stage actors in general, and to the almost non-existent literature on Filipino professional stage actors in particular. Understanding the status and problems of the lives of professional stage actors should be the first step in further improving their plight and in appreciating more their central role in the continued existence of theatre as a cultural practice.